Tell Me Where You Live… How the Perceived Entitativity of Neighborhoods Determines the Formation of Impressions About Their Residents - Bernardo, Fátima; Palma-Oliveira, José Manuel (Frontiers in Psychology, 2022)
The studies presented here apply the concept of entitativity in order to understand how belonging to a particular geographical area – neighborhood - can determine the way others organize information and form impressions about area's residents. In order to achieve this objective, 3 studies were carried out. The first study aims to verify if a neighborhood varies in terms of perceived entitativity, and identify the physical and social characteristics of this neighborhood that are more strongly associated with the perception of entitativity. The study 2 and 3 used an experimental paradigm to explore how people's perceptions of neighborhoods' entitativity influenced their impressions of residents. To activate stereotypes, study 2 used the name of real neighborhoods, and study 3 employed only a set of pictures of unknown neighborhoods. The results show that the neighborhoods vary significantly with the regard to the perception of entitativity, and a set of physical attributes of place were strongly related with entitativity. The results showed that, independent of stimuli, the neighborhoods perceived as highly entitative, the supposed residents were subject to more extreme and quicker trait judgments, supported by greater confidence on the part of perceivers. Study 3 also reported that in highly entitative neighborhoods, the perceivers transferred more traits from the group to individual members. These results provide strong evidence that physical structure of neighborhoods imply different entitatity judgments that influences the way in which residents are perceived.